Penyuluhan Pemantauan Tumbuh Kembang Anak Prasekolah Tk Al-Mubtadi Desa Padang Tikar Kabupaten Kubu Raya 2024 - Nur Latifah; Khulul Azmi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Motor development is the process of growth and development of a child's ability to move. Basically, this development develops in line with the maturity of the nerves and muscles of the child. The form of community service activities carried out is the implementation of counseling to mothers about the level of development of children under five to pre-school. The population of preschool children in Indonesia is around 10% of the total population. The quality of growth and development of preschool children in Indonesia needs serious attention because they are the future generation of the nation. For this reason, children need to receive good nutrition, adequate stimulation and access to quality health services. including early detection and intervention of growth and development deviations, so that they can grow and develop optimally in accordance with their genetic potential and be able to compete in the global era